Integration Of Social Entrepreneurship, Csr, And Triple Helix In The Dtsen Framework For Empowering Msmes - Ananda Paula Sabrina; Harry Z Soeratin (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
This study analyzes the integration of Social Entrepreneurship (SE), Corporate Social Responsibility (CSR), and the Triple Helix Model within the framework of the Digital and Sustainable Entrepreneurship Nation (DTSEN) as a strategy to strengthen sustainable entrepreneurship and empower MSMEs in Indonesia. Using a Systematic Literature Review of 15 selected articles, the study reveals that SE drives social innovation and enhances MSME resilience, while CSR provides strategic resources such as funding, training, and technological support. The Triple Helix functions as a collaborative framework connecting academia, government, and industry to build a more inclusive entrepreneurial ecosystem. The analysis identifies a theoretical gap due to the absence of an integrative model explaining the causal relationship among the three elements, as well as empirical gaps stemming from limited quantitative and longitudinal studies measuring their impact on MSMEs. Contextual challenges, including digital readiness disparities and regional capacity differences, further complicate implementation. These findings highlight the need for a comprehensive, adaptive integrative model to support DTSEN and strengthen Indonesia’s sustainable economic development.